2013
DOI: 10.5966/sctm.2013-0146
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of Drug-Induced Liver Injury Using Stem Cell-Derived Populations

Abstract: It has been observed that there is an imperative to develop predictive human systems that more effectively study and/or prevent the onset of liver disease and decompensated organ function. A serum‐free, scalable, and shippable cell‐based model that faithfully predicts the potential for human liver injury has been developed. Such a resource has direct application in human modeling, and, in the future, could play an important role in developing renewable cell‐based therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
101
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 23 publications
5
101
0
1
Order By: Relevance
“…To date, numerous studies in rodents have shown that predifferentiated ESC transplantation can reverse acute fulminant hepatic failure 6,50, 51, 52, 53, 54. In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver.…”
Section: Resultsmentioning
confidence: 99%
“…To date, numerous studies in rodents have shown that predifferentiated ESC transplantation can reverse acute fulminant hepatic failure 6,50, 51, 52, 53, 54. In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver.…”
Section: Resultsmentioning
confidence: 99%
“…For example, maintenance of hiPSC-derived hepatocytes for up to two weeks was reported, enabling repeated-dose chronic exposure to hepatotoxic compounds. 146,147 Studies on MPCC with hiPSC-derived human hepatocytes 148 indicate a similar sensitivity toward drug toxicity as observed in MPCC using PHH. 51 In addition, hepatocytes generated from pluripotent stem cells have been successfully applied in in vitro studies on infectious diseases like hepatitis B and C infection 149,150 or malaria pathogenesis.…”
mentioning
confidence: 99%
“…Protocols to differentiate human embryonic stem cells and human induced pluripotent stem cells into hepatocytes have improved immensely in recent years, and now hepatocyte cultures with high purity and many characteristics of functional hepatocytes can be obtained from hPSC (Brolen et al, 2010;Si-Tayeb et al, 2010;Touboul et al, 2010;Yildirimman et al, 2011;Hannan et al, 2013;Ulvestad et al, 2013;Szkolnicka et al, 2014). The fact that these cells can be derived in a robust and reproducible fashion from a well-characterized source makes them very attractive as a toxicity assessment model.…”
Section: Introductionmentioning
confidence: 99%